Knautia goecmenii (Caprifoliaceae): an unexpected caespitose suffrutescent new species from the Western Anatolia, Turkey - Yildirim, Hasan; Özdöl, Tuğkan; Can, Ilgin Deni̇z; Erdem, Seval; Oğur, Erdi̇nç; Özüdoğru, Bariş (Phytotaxa, 2022)
Knautia goecmenii, from Nif Mountain (İzmir) in western Anatolia (Turkey), is described as a new species based on morphological and molecular evidence. Its phylogenetic relationships within the genus are provided based on the nuclear-encoded ribosomal internal transcribed spacer (ITS) region. Bayesian and Maximum Likelihood analyses of the molecular data clearly showed that K. goecmenii falls into a clade together with morphologically irrelevant annual species from sections Knautia and Tricheroides. From a morphological perspective, by having a suffrutescent and caespitose habitus with very rich stemmed base (up to 152 stems) without basal leaf rosettes and showing very pale whitish-lilac flowers, K. goecmenii is placed in a unique position within genus Knautia. Both the main morphological features of K. goecmenii and its phylogenetic position make difficult to accommodate it any extant Knautia sections. Finally, the International Union for Conservation of Nature (IUCN) threat category is assessed and observations on the ecology of the only known population of this rare species are noted.